Skema Pembayaran Pada Kontraktor Dengan Hasil Cashflow Yang Optimal (Studi Kasus Proyek Pembangunan Gedung Politeknik Negeri Madiun) - Arif Bakhtiar E, Mohammad (JURNAL AGRI-TEK, 2015)
Partly contractor yet understand about condition of three constraint the day, quality and charge. Blends with 3 condisition will achieve the purpose project that benefit all parties involved in this. Project cost often poorly conceived as one resources that can affect smoothness current financial and affect profits in the projects. Smoothness cash flow is influenced system payment on a project. To know payment system most favorable then held research on project Pembanguan Gedung Politeknik Negeri Madiun to make a scheme payments give maximal profit contractor. With the help of Microsoft Project can be made condition schedule EST, LST and so shift that will influence the cashflow and made scheme payment without earnest money; money advanced 10 %, 15 % and 20 %. The scheme payment of which there are shows that the payment system that give an advantage is maximum monthly repayments money advanced 20 % in the condition of EST with a value to the Rp 447.144.510,0 and profit 9,61 %Key words: Cash flow, PDM, Earliest Start Time, Latest Start Time